Perioperative prothrombin complex concentrate and fibrinogen administration are associated with thrombotic complications after liver transplant - Dehne, Sarah; Riede, Carlo; Klotz, Rosa; Sander, Anja; Feisst, Manuel; Merle, Uta; Mieth, Markus; Golriz, Mohammad; Mehrabi, Arianeb; Büchler, Markus W.; Weigand, Markus A.; Larmann, Jan (Frontiers in Medicine, 2022)
Background Use of intraoperative prothrombin complex concentrates (PCC) and fibrinogen concentrate administration has been linked to thrombotic events. However, it is unknown if its use is associated with thrombotic events after liver transplant. Methods and analysis We conducted a post hoc analysis of a prospectively conducted registry database study on patients who underwent liver transplant between 2004 and 2017 at Heidelberg University Hospital, Heidelberg, Germany. Univariate and multivariate analyses were used to determine the association between PCC and fibrinogen concentrate administration and thrombotic complications. Results Data from 939 transplantations were included in the analysis. Perioperative PCC or fibrinogen administration was independently associated with the primary composite endpoint Hepatic artery thrombosis (HAT), Portal vein thrombosis (PVT), and inferior vena cava thrombosis [adjusted HR: 2.018 (1.174; 3.468), p = 0.011]. PCC or fibrinogen administration was associated with the secondary endpoints 30-day mortality (OR 4.225, p < 0.001), graft failure (OR 3.093, p < 0.001), intraoperative blood loss, red blood cell concentrate, fresh frozen plasma and platelet transfusion, longer hospitalization, and longer length of stay in intensive care units (ICUs) (all p < 0.001). PCC or fibrinogen administration were not associated with pulmonary embolism, myocardial infarction, stroke, or deep vein thrombosis within 30 days after surgery. Conclusion A critical review of established strategies in coagulation management during liver transplantation is warranted. Perioperative caregivers should exercise caution when administering coagulation factor concentrate during liver transplant surgery. Prospective randomized controlled trials are needed to establish causality for the relationship between coagulation factors and thrombotic events in liver transplantation. Further studies should be tailored to identify patient subgroups that will likely benefit from PCC or fibrinogen administration.